Analisa Prestasi Siswa Berdasarkan Kedisiplinan, Nilai Hasil Belajar, Sosial Ekonomi dan Aktivitas Organisasi Menggunakan Algoritma Naïve Bayes - Devi Yunita; Perani Rosyani; Resti Amalia (Teknik Informatika Universitas Pamulang, 2018)
Student achievement is needed to measure the level of knowledge, intelligence, and skills of a person. Data mining is a combination of various fields of science, namely statistics, artificial intelligence, and databases. The purpose of education for students is to be able to change attitudes, perceptions, instill good behavior and instill knowledge and character. The purpose of this study is to be able to find out student achievement during learning as a school evaluation material to improve teaching patterns for students to be more accomplished. Research using the Naïve Bayes Algorithm produces a fairly good value of accuracy of 89%. the results of this study are expected to help to monitor early student academic achievement, in order to improve student achievement and quality.